Gram-Negative Bacteremia: Epidemiology and Antimicrobial Resistance in Qatar (American Journal of Medical Science and Innovation, 2024)
One of the major causes of morbidity and mortality in hospitalised patients is the presence of gram-negative bacteremia (GNB) in blood. The developed resistance among the bacteria poses a significant challenge for treatment. The study aimed to identify the gram-negative patient’s epidemiological risk factors, antimicrobial susceptibility patterns, and clinical outcomes. A retrospective observational study of adult in-patients with gram-negative bacteremia was conducted between January 2019 and December 2020 in the 320-bed general hospital in Qatar. Data on demographics, antimicrobial resistance, source of infection, and treatment were collected. The primary outcomes were patients’ cure, death, or relapse. Total of 357 patients were identified with bacteremia, the most common sources being urinary tract infections (39.6%), intra-abdominal infections (28%), and lower respiratory tract infections (9%). The mean duration of the intravenous and oral antibiotics administration was 14 days. Surgical source control was performed in 35.7% of patients. Common pathogens were Escherichia-coli (47.2%), Klebsiella pneumoniae (16.4%), Salmonella enterica serotype Typhi (10.6%), and Pseudomonas aeruginosa (7.8%). 67.32% fully susceptible strains, 31.56% extended-spectrum beta-lactamase (ESBL) producing bacteria, and 1.11% multidrug-resistant organisms (MDROs) were among the isolates. Most infections (68%) were cured, but 5% had recurrence within 90 days of admission. Infection-related mortality was 8%, and death due to non-infectious causes was 2%. In conclusion, Gram-negative BSIs are severe infections with increasing antimicrobial resistance, primarily caused by ESBL-producing bacteria. High mortality rates are linked to diabetes, age, and hospitalisation, necessitating antibiotic treatment optimisation.